Perdagangan Manusia Menurut Teologi Tubuh dan Seksualitas Dalam Perspektif Yohanes Paulus II - Valdo, Fabrisio Olie; Haryadi, Dominikus Setio; Nugroho, Ambrosius Gerin; Letsoin, Yetva Softiming (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2024)
This paper is about Pope John Paul II's views on the theology of the body and sexuality. Pope John Paul II intended to show that the human body is God's way of revealing Himself. The transcendent God, who is invisible, who cannot be seen with the human sense of sight, can be known by human beings, His creation, through the human body. The body is more than just the physically visible body, what is outwardly visible, what is capable of being sensually perceived, the body is also capable of showing a reality that goes beyond the outward dimension alone. The body is able to make visible what is invisible; the spiritual and the divine. The Theology of the Body according to John Paul II aims to transfer into the reality of the world, a fundamental interpretation of the fundamental meaning of the human body. The issue of human trafficking that occurs today does not show respect for the human body as God's creation. Human trafficking is an affront to the dignity of the human body from the perspective of John Paul II's theology of the body.